The synthesis and chemistry of macrolactones - Cook, Lawrence D. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
The work herein presented is an investigation into the methodology of macrolactonisation via an intramolecular acylative cleavage of a tetrahydrofuran ring. The thesis is divided into three Chapters: an introduction outlining the history and biological role of macrolactones, and the techniques currently being exploited in their synthesis; an improvement upon the technique of macrolactonisation via intramolecular acylative cleavage of tetrahydrofuran rings; and progress towards the total synthesis of the naturally occurring macrolactone curvularin.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin